Urban void as an urban catalyst bridging the gap between the community - Aleha, Anum; Zahra, Syeda Mahwish; Qureshi, Sabeen; Marri, Sohrab Ahmed; Siddique, Sarah; Hussain, Samar Shamim (Frontiers in Built Environment, 2023)
Due to the increase in population, there are fewer open spaces creating Urban Voids in cities nowadays. However, the opportunities made available to people by urban voids adequately indicate the necessity and significance of urban open spaces. The lack of proper planning and good perception of the place led to the formation of lost spaces. These lost spaces are everywhere, and treating as they are waste spaces. By reclaiming these urban voids we can change them into public gathering spaces, pocket parks or any user friendly space admire by the users. The objective of the study is to determine, why these waste spaces called urban voids and are not utilised to their full potential. The identified area for case study is near railway colony Multan. The selected area is L-shaped connected with under flyover which is creating huge void. The spatial methodology, which is based on identifying physical condition, and surveys, which depends on user ratings, were the foundations of the research methodology. Users assigned ratings for the space performance, which was determined by spatial analysis approach and differed in terms of space structure and attributes. A total of 280 participants (118 females and 162 men) rated the technical, functional, and aesthetic performance of the spaces they occupy using a Likert attitude scale, with 70 individuals from each of the identified connected urban voids under flyover. The results showed that space performance affects user satisfaction and space usage level after design interventions. Keywords: Urban Voids, Urban Catalyst, Space Performance, User Satisfaction, Urban Open Spaces.